RESEARCH ON READINESS FOR JOB CREATION THROUGH ONES OWN AGRIBUSINESS STARTUP - Vojnović, Boško; Stefanović, Vidoje; Vojnović, Dragana; Perović, Milorad (Economics of Agriculture, 2014)
This paper examines the problems of jobs, employment, staff hiring in the agriindustrial complex, job description and requirements, theoretical and practical job cost indicators, and the willingness of our people to create new jobs by starting up their own private agribusiness. The results indicate a chronic lack of private funds necessary for every new business as well as the inevitability of borrowing. Potential entrepreneurs know the advantages and the disadvantages of solo and partnership business; however, they do not have any potential partners in sight. Almost a half of them have their own facilities and arable land etc. as a material base; however, they do not know what else is needed for a business to operate properly. In general, they understand the importance of education and training for any future business.